Capacity building of cadres in the preparation of MP-ASI formula as a family nutrition booster based on Kelakai: A critical innovation (Care for Stunting) for families. - Herda Ariyani; Aziza Fitriah; Rizqi Amalia Aprianty; Dyta Setiawati Hariyono; Dewi Nurhanifah; Muhammad Anshari; Anna Diniati; Firni Noviyanti Fatimah; Pitria Ulfah; Saputri Nurrifanti Dewi; Siti Lailan Azima (UMBanjarmasin, 2023)
In addition to being a national health issue, stunting is a worldwide health concern because it lowers productivity, inhibits IQ, and causes disease in human resources. The purpose of this activity is to enhance cadres' proficiency in processing MP-ASI using the traditional knowledge of kelakai leaves in Samuda village, Belawang District, Barito Kuala Regency, as well as their knowledge base about stunting and MP-ASI. The KPM Cadres (Human Development Cadres), Posyandu Cadres, TPK (Family Assistance Team), and village food cadets are the targets of this community service project. The initial step in this activity's methodology is creating an MP-ASI Formula Book using Kelakai (Stenochlaena palustris (Burm.f.) Bedd. Second, the practice of directly preparing meals and educating people about health and nutrition The information is delivered through interactive lecture and discussion methods as well as simulations. This community service was carried out over two meetings. The location for this service activity is at the Samuda Village Hall. The results of the activity showed that there was an increase in knowledge after the training activity was held, namely that the level of understanding increased significantly from 0% to 100% in two aspects of knowledge, namely MP-ASI criteria and family medicinal plants that stimulate appetite. The results of the analysis of different tests showed that there was a difference in the mean knowledge scores of participants before and after being given the training (p = 0.000). Conclusion: The application of nutritional literacy with the help of formula books and job sheets has been proven to be able to increase cadres' knowledge and skills and effectively foster innovation in making MP-ASI formulas as potential family-based family nutrition boosters